Confirmation of pygmy sperm whale, Kogia breviceps from Palk Bay, India through Cytochrome Oxidase1 (COI) sequence: Pygmy sperm whale, Kogia breviceps from Palk Bay, India - Chandrasekar, K; K, MADHU MAGESH; KV, Vishnu; Kumar, Sendhil; Cubelio, Sherine; N, Saravanane; K, SIVAKUMAR (J. Cetacean Res. Manage., 2021)
The identity of a stranded cetacean from the Palk Bay has been confirmed as a pygmy sperm whale (Kogia breviceps) by the partial sequencing of mitochondrial gene cytochrome oxidase subunit-I (COI). The specimen was unambiguously discriminated from the COI sequence of Kogia sima by matching exactly with the sequence of K. breviceps. Stranding events of the pygmy whales are considered to be uncommon. The sequence developed for K. breviceps is the first of its kind attempt from Indian waters.